Pemahaman Tekstual dan Kontekstual terhadap Hadits Larangan Menafsirkan Al-Qur'an Dengan Al Ra'y - Abd Majid Abror (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Tafsir bi al-ra'y is an interpretation of the Qur'an using al-ra'yu, which has several meanings, among them al i'tiqad (understanding, tradition), al-Ijtihad, al qiyas (analogy) as the term ahl al¬ra'y is often used to refer to the ashab al qiyas. (analogy users). As an understanding of the meaning of al ra'y in the context of hadith, considering the hadith emphasizes the meaning of al rayu as reason ansich (without based on knowledge / bil gair 'ilm). the meaning of al ra'y which is forbidden in the content of the hadith is an interpretation that is based solely on reason alone by not paying attention to the history or method or knowledge related or not by the principle of syar'i, more or less doing lies on the Qur'an. When associated with the interpretation of bi al-ra'yi is very different because the interpretation of bi al-ra'yi although dominated by reason but still also return to the basis of syar'i and the methods that apply during the interpretation, basically the interpretation of bi al ra'y that still meets the requirements of interpretation that is the study of language, rne pay attention to the history related to the situation and conditions when the verse comes down, understand nasikh mansukh and others are also by the principle of syar'iy , then it is permissible, on the contrary that only use reason alone, more arises from his lust, then the interpretation of bi al ra'y like this is forbidden.